Nocturnal oesophageal motor activity is dependent on sleep stage. Issue 12 (December 1993) - Castiglione, F; Emde, C; Armstrong, D; Schneider, C; Bauerfeind, P; Stacher, G; Blum, A L
Abstract : Simultaneous overnight oesophageal pH and manometric and sleep electroencephalographic recordings were performed in eight healthy subjects, aged 20-38 years, to test the hypothesis that the frequency of primary, swallow related contractions decreases progressively with deeper sleep stages whereas the frequency of secondary contractions remains constant throughout the night. During the nocturnal period (2300 to 0700), periods of oesophageal motor quiescence were interspersed by clusters of contractions detected 5 and 15 cm above the lower oesophageal sphincter. Primary contractions decreased in frequency from 1.42/min (median) during arousal periods to 0.22/min during stage 1 sleep, 0.05/min during stages 2 to 4 combined, and 0.03/min during rapid eye movement (REM) sleep. Secondary contractions were also most frequent during arousal periods (0.51/min) and they, too, decreased in frequency during stage 1 (0.35/min) and stages 2 to 4 combined (0.08/min). During REM sleep, however, the frequency of secondary contractions increased (0.50/min) to levels noted during arousal and stage 1 sleep. Compared with primary contractions, secondary contractions had a lower amplitude (51.9 hPa v 76.0 hPa; p = 0.0078) and a shorter duration (3.08 v 4.06 s; p = 0.0078). The results of this study suggest that there is no intrinsic oesophageal motor activity in the absence of a stimulatory input from the central nervous system and that the increased number of secondary contractions during REM sleep may be a result of an REM related increase in autonomic nervous system activity although a temporary decrease of efferent inhibitory influences cannot be ruled out. Nocturnal contraction clusters comprise both primary contractions during arousals and stage 1 sleep and secondary contractions during REM sleep.